Stock market impact of cross-border acquisitions in emerging markets - Pehr-Johan Norbäck; Lars Persson (Research Institute of Industrial Economics (IFN), 2019)
Entry by multinational enterprises (MNEs) into emerging markets has increased substantially over the last decades. Many of these MNE entries have taken place in concentrated markets. To capture these features, we construct a strategic interaction model of MNE cross-border acquisition and greenfield entry into an oligopolistic market. We provide an event study framework suitable to derive predictions for the stock market values of MNE entries. We show that share values of acquirers will increase when an acquisition is announced if and only if the domestic assets are not too strategically important. If there is risk associated with cross-border M&As, we show that such risks reduce the likelihood and the acquisition price of cross-border M&As. These mechanisms provide an explanation for why acquirers tend to overperform when acquiring in emerging markets but underperform when acquiring in developed markets. We also show that shareholders of targets firms in emerging markets may benefit from not selling their firms too early in the development phase.
Keywords: F23; G34; L13; 330; FDI; Cross-Border Mergers and Acquisitions; Stock Market Value; Emerging Markets